SOLPS-ITER simulations of the TCV divertor upgrade. (5th July 2019) - Wensing, M; Duval, B P; Février, O; Fil, A; Galassi, D; Havlickova, E; Perek, A; Reimerdes, H; Theiler, C; Verhaegh, K; Wischmeier, M
Abstract: The effect of the upcoming TCV divertor upgrade on the distribution of neutrals and the onset of detachment is studied using 2D transport code simulations. The divertor upgrade is centered around the installation of a gas baffle to form a divertor chamber of variable closure. SOLPS-ITER simulations predict that the baffle geometry selected to be installed in TCV in 2019 increases the divertor neutral density by a factor ∼5 and the neutral compression by one order of magnitude in typical TCV single null, Ohmic heated scenarios (330 kW). The compression increases further with the addition of auxiliary heating systems (1.2 MW). Simulations show that volumetric power losses in the divertor increase giving access to deeper detachment for given upstream densities and heating power. Predictions for observations by various TCV diagnostics, including baratrons, divertor spectrometer and visible camera systems, are presented to guide the experimental verification of the efficiency of the divertor baffles.